Self-Perception of Gerontoism according to Social Support and Family Functionality - Herbert Rubens KOCH FILHO; Luiza Foltran de Azevedo KOCH; Solena Ziemer KUSMA; Sérgio Aparecido IGNÁCIO; Simone Tetu MOYSÉS; Luciana Ribeiro Azevedo ALANIS; Marilisa Carneiro Leão GABARDO; Samuel Jorge MOYSÉS (Tehran University of Medical Sciences, 2019)
Background: The gerontoism, a neologism adopted here, is a form of discrimination regarding age and can occur in rational, emotional, and behavioral contexts, and could be influenced by many factors. This study aimed to identify if the social support and the family functionality interfere in the self-perception of gerontoism. Methods: Participants were 376 elderly in good physical and mental condition. They participated in the Group Living organization in the Municipality of Curitiba, State of Paraná, Brazil, in 2012.  Information was collected about sociodemographic profile using a structured questionnaire. The social support, the family functionality, and the self-perception of gerontoism were defined by the Medical Outcomes Study, the Family APGAR index, and Ageism Survey, respectively. The variables were analyzed by Pearson's correlation coefficient, One Way ANOVA, Tukey's HSD test, and the Student's t-test. Results: Most of the participants came from small cities from the interior (48.7%), were female (94.4%), with age ranging 60-69 yr-old (45.5%), whites (76.1%), widowers (47.1%), with children (93.9%), with low schooling (55.3%), with family income from 1-2 minimum wage (31.4%), and retirees not working (44.1%). It was not observed correlation between sociodemographic variables and self-perception of gerontoism. Statistical significance was observed between self-perception of gerontoism and social support (r= -0.26, P=0.00), and between the self-perception and family functionality (r = -0.28, P=0.00). Once the scores of self-perception of gerontoism increased, the ones from social support and family functionality, decreased. Conclusion: Lower self-perception of gerontoism was observed in elderly with higher social support and family functionality.